Gender Based Violence and LGBTQI+ Migrants: Assessing Visibility/Invisibility Tactics through the Italian Reception System - Fedele, Valentina; Garofalo, Sabrina (PARTECIPAZIONE E CONFLITTO, 2025)
Persecutions and discrimination based on Sexual Orientation, Gender Identity and Expression, and Sex Characteristics-diversity (SOGIESC-diversity) are recognized as reasons to claim asylum. Despite this, data on the impact of gender-based violence (GBV) on LGBTQIA+ migrants are limited, both from a quantitative and a qualitative point of view. This sustains an enduring invisibilization of LGBTQIA+ migrants, through migration paths and in reception centers. Using Collins' matrix of domination as a framework, this article provides a qualitative analysis of the experience of the project "MigrAzioni" organised by an Italian Association for the rights of LGBTQIA+ people in the South of Italy. A mixed method approach has been used, collecting both official documentation and the experience of SAI reception centers' operators, LGBTQIA+ right activists and migrants. The article highlights the articulation of visibility/invisibility in the LGBQTIA+ migrants' experience, underlining the different ways the latter is intersected by forms of GBV, institutional processes, cultural and social models, gender stereotypes, but also involving daily tactics enacted in liminal spaces between the subjects and the society.